Transition from a singly vergent to doubly vergent wedge in a young orogen: The Greater Caucasus. Issue 11 (4th November 2014) - Forte, Adam M.; Cowgill, Eric; Whipple, Kelin X.
Abstract The Greater Caucasus Mountains, due to their youth (~5 Ma), provide an opportunity for insight into the early stages of orogen development during continent‐continent collision. However, their recent tectonic evolution and first‐order architecture remain unclear. Here we investigate the evolution of the orogen by integrating new observations of the fluvial geomorphology and neotectonics of the range with prior work on seismicity, geodetic strain, bedrock geology, and foreland basin structure. We find that the range contains four zones along strike that differ in structural architecture, topography, and first‐order tectonic history. In particular, two south directed, singly vergent zones at the western and eastern tips of the orogen are separated by both a central doubly vergent zone that is dominated by north directed deformation and an eastern doubly vergent zone in which south directed thrusting dominates. We hypothesize that the along‐strike changes in vergence and locus of deformation reflects different stages in the development of a doubly vergent orogen, with the tips of the range preserving an early, singly vergent form and the center recording a more advanced orogen. The differences between the two doubly vergent zones seem to be driven by the initial stages of collision between the structurally thickened crust of the Greater and Lesser Caucasus orogens, which initiated at ~5 Ma.